Zirconium-89 Labeled Antibodies: A New Tool for Molecular Imaging in Cancer Patients - Floor C. J. van de Watering (BioMed Research International, 2014)
Antibody based positron emission tomography (immuno-PET) imaging is of increasing importance to visualize and characterize tumor lesions. Additionally, it can be used to identify patients who may benefit from a particular therapy and monitor the therapy outcome. In recent years the field is focused on 89Zr, a radiometal with near ideal physical and chemical properties for immuno-PET. In this review we will discuss the production of  89Zr, the bioconjugation strategies, and applications in (pre-)clinical studies of  89Zr-based immuno-PET in oncology. To date, 89Zr-based PET imaging has been investigated in a wide variety of cancer-related targets. Moreover, clinical studies have shown the feasibility for 89Zr-based immuno-PET to predict and monitor treatment, which could be used to tailor treatment for the individual patient. Further research should be directed towards the development of standardized and robust conjugation methods and improved chelators to minimize the amount of released Zr4+ from the antibodies. Additionally, further validation of the imaging method is required. The ongoing development of new 89Zr-labeled antibodies directed against novel tumor targets is expected to expand applications of  89Zr-labeled immuno-PET to a valuable method in the medical imaging.